Parameters controlling weld bead profile in conduction laser welding - Ayoola, W.; Suder, Wojciech; Williams, Stewart W. (Elsevier, 2017)
In laser welding and other processes, such as cladding and additive manufacturing, the weld bead geometry (depth of penetration and weld width) can be controlled with different parameters. A common practice is to develop process parameters for a particular application based on an engineering approach using the system parameters i.e. laser power and travel speed. However, in such a case the process is optimised for a particular system only. This study is focused on understanding of the phenomena controlling the weld profile in conduction welding for a wide range of beam diameters from 0.07 mm to 5.50 mm. It has been shown that the weld bead geometry can be controlled by the spatial and temporal distribution of laser energy on the surface of workpiece, such as power density, interaction time and energy density. This means that similar depths of penetration can be achieved with various optical set-ups. It has been also found that it is more difficult to achieve pure conduction welds with small beam diameters, which are typically used in powder bed additive manufacturing, due to high conduction losses and low vaporisation threshold.
Keywords: Conduction laser welding; Weld bead profile; Interaction parameters; Beam diameter